Performance Enhancement of the DPC Control Based on a VGPI Controller Applied to a Grid Connected PV System - Boukhalfa, M.; Benaissa, A.; Bengourina, M. R.; Khoudiri, A.; Boudiaf, M. (Engineering, Technology & Applied Science Research, 2022)
Even though the PI controller is among the most widespread controllers in photovoltaic (PV) systems, it presents overshoots and undershoots in the tracking trajectory mode. This major disadvantage remains an open problem. In the current paper, a Direct Power Control (DPC) of a three-phase grid-connected PV system based on a Variable Gain PI (VGPI) controller is developed to remove the overshoots and undershoots in the classical PI controller. The proposed control system has been tested in the Matlab/Simulink environment. The simulation results demonstrate the feasibility and robustness of the proposed method in terms of overshoots, undershoots, and current quality.